1970
DOI: 10.1002/aja.1001290405
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the corpus luteum in the ewe: Changes during the estrous cycle and early pregnancy, and in response to some experimental treatments

Abstract: A technique, developed for the objective histological evaluation of the corpus luteuin of the sheep, was applied to normal cyclic and pregnant ewes as well as to ewes subjected to various experimental treatments. Gross histological regression of the corpus luteum progressed rapidly between days 15 and 17 of the estrous cycle. Similar regressive changes did not occur in pregnant ewes; up to day 40, the oldest stage studied, corpora lutea of early pregnancy were similar in appearance to those of mid-cycle.Stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The morphology of the CL has already been described in detail for many species [26][27][28][29][30][31]. Histologic and laparoscopic methods are used to determine the estrous cycle phase [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of the CL has already been described in detail for many species [26][27][28][29][30][31]. Histologic and laparoscopic methods are used to determine the estrous cycle phase [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Whenever possible samples of embryos and embryonic membranes were also collected for histological evaluation, the membranes being prepared by the methods of Moog and Lutwak·Mann (1958). Smears were prepared from the fresh lumenal contents of each ewe to enable a check for bacterial contamination to be made, and corpora lutea were recovered, weighed, and processed by the methods of Thwaites and Edey (1970).…”
Section: Methodsmentioning
confidence: 99%
“…During the second phase of degeneration and resorption, the duration of which varied between individuals and with time of embryonic death, gradual resorption of the embryonic debris occurred. Examination of Tables 3-5 indicates that in no case did corpus luteum regression (as assessed by a sharp increase in the proportion of type 4 lutein cells- Thwaites and Edey 1970) or return to service occur until virtually all embryonic debris had been removed from the uterus. In other words, the major reason for delayed return to service after embryonic death appears to be delayed embryonic resorption.…”
Section: (F) Day 19 Colchicine Treatmentmentioning
confidence: 99%
“…The well developed corpus luteum in this investigation reveals the presence of four types of cells. The first and second types are of granulosal ori in and are identical with the type 2 lutein cells, the so-called "blossom cel P s" described by THWAITES and EDEY (1970) in sheep. The type I described by the latter author is identical with the type 111 in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…Although the histology of these organs has been studied fully in different animal species and in man (ELDER, 1925, HAMMOND, 1927, Moss et al, 1954and THWAITES and EDEY, 1970, no literature on the buffalo was found.…”
Section: Introductionmentioning
confidence: 99%